Water Reclamation and Reuse. (1st October 2018) - Sun, Huijuan; Zhang, Huixin; Xu, Rui; Zou, Xin; Liu, Yang
Abstract : Literature published in 2017 related to water reclamation and reuse is reviewed in four categories: sustainable reuse, treatment technology, implementation, and assessment and management. The development and improvement of conventional treatments and new methods that afford safe wastewater reuse are examined.